2008
DOI: 10.1097/mao.0b013e31817dad57
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Cartilage Palisades and Fascia in Type 1 Tympanoplasty in Children

Abstract: Palisade tympanoplasty in children yielded good anatomic and functional results. The anatomic results obtained using this technique were superior to those obtained using temporalis muscle fascia. Children who underwent Type 1 tympanoplasty with palisaded cartilage had equivalent postoperative audiometric results compared with children who underwent Type 1 tympanoplasty with temporalis fascia. Thus, palisade cartilage tympanoplasty is an effective technique for both tympanic membrane closure and hearing improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
81
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 24 publications
5
81
0
Order By: Relevance
“…In elderly patients, the mental state and metabolic (diabetes mellitus) and cardiovascular diseases are more important than the age, whereas in children (especially in those younger than 6 years of age), the risk of perforation or retraction is related to underdeveloped immunity, serous otitis media, and recurring middle ear infections [9,20] . Furthermore, the small middle ear structure and narrow external ear canal lower the success of tympanoplasty [20] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In elderly patients, the mental state and metabolic (diabetes mellitus) and cardiovascular diseases are more important than the age, whereas in children (especially in those younger than 6 years of age), the risk of perforation or retraction is related to underdeveloped immunity, serous otitis media, and recurring middle ear infections [9,20] . Furthermore, the small middle ear structure and narrow external ear canal lower the success of tympanoplasty [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, cartilage or composite cartilage grafts are more resistant to infections, middle ear pressure, and lack of capillary feed. Therefore, it can be preferred in revision tympanoplasty in which the risk of perforation or retraction is higher [4,5,6,8,9] .…”
Section: Introductionmentioning
confidence: 99%
“…Albirmawy (20) evaluated 82 pediatric patients who underwent type I tympanoplasty surgery, and he found the success rate to be 95% in the cartilage group and 76.2% in the fascia group. In addition, Ozbek et al (21) compared the results of type I tympanoplasty surgeries performed using palisade cartilage technique and a fascia graft and found that the anatomical success rate was significantly higher in the cartilage group. Despite the fact that anatomical success rates are higher for cartilage than for fascia, there are still doubts about the use of cartilage, because it is assumed that such a thick and rigid material can affect post-operative hearing in negative way.…”
Section: Discussionmentioning
confidence: 99%
“…Although better hearing outcomes have been documented in type III tympanoplasty using synthetic ossicular grafts as demonstrated in various past literatures, a substantial proportion of the patients require revision surgery because of displacement and extrusion of graft in the postoperative period [5][6][7]. There are very few studies conducted in the past showing cartilage being exclusively used for ossiculoplasty and tympanic membrane grafting (classical type III tympanoplasty) in canal wall down mastoidectomy [8] although it has been widely used for type I cartilage tympanoplasty for the reconstruction of a large central perforation and for the repair of attic defect in limited attic disease [9][10][11][12]. A similar study conducted by Quaranta et al [13] taking patients undergoing cartilage tympanoplasty in intact canal wall mastoidectomy has demonstrated 100% anatomical closure of tympanic membrane without any extrusion of cartilage graft in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%